The isotopic signature of particulate organic C and N in bottom ice: Key influencing factors and applications for tracing the fate of ice‐algae in the Arctic Ocean. Issue 1 (30th January 2013) - Pineault, Simon; Tremblay, Jean‐Éric; Gosselin, Michel; Thomas, Helmuth; Shadwick, Elizabeth
Abstract: [1] The isotopic, taxonomic, and nutrient dynamics of protist communities at the bottom of first‐year sea ice were studied for a wide range of ice conditions during the spring‐summer transition in the southeast Beaufort Sea. In bottom ice, total protist abundance ranged from 0.07 to 9.94 × 10 9 cells m –2 and chlorophyll a biomass ranged from 0.33 to 110 mg m –2 . Both variables were positively related to the concentrations of nitrate, silicic acid, and phosphate at the ice‐water interface, with r 2 values between 0.63 and 0.79. Results showed that the δ 13 C of sympagic (ice‐associated) particulate organic matter (POM) (–27.1 to –11.4‰) was mainly influenced by ice protist stocks and dissolved inorganic carbon availability. Flagellated cells maintained a low δ 13 C relative to diatoms. The δ 15 N of POM (3.9 to 9.4‰) could not be explained by any of the variables considered and showed considerable overlap with the pelagic δ 15 N‐POM (0.0 to 10.3‰). Detailed analyses of δ 13 C‐POM through size fractionation and settling experiments along with a short temporal study of the interaction between sympagic and pelagic communities confirmed or demonstrated that (1) the analysis of stable C isotopes is a valuable tool to trace the flow of ice‐derived matter, (2) sympagic POM contributes substantially to suspended pelagic biomass during release episodes, and (3) ice‐grown autotrophic flagellated cells have a strong potential to interact with the pelagic biota in the coastal Arctic Ocean. This study highlights the need to carefully evaluate stable isotope dynamics before assessing food web interactions or the fate of POM in seasonally ice‐covered waters. Key points: d13C of sympagic POM is controlled by ice protist stocks and DIC availability The presence of sympagic POM in the water column can be traced with d13C Sympagic flagellated cells have a strong potential to contribute to pelagic POM